Effects of the IMF Direction on Atmospheric Escape From a Mars‐like Planet Under Weak Intrinsic Magnetic Field Conditions. Issue 3 (10th March 2021) - Sakai, Shotaro; Seki, Kanako; Terada, Naoki; Shinagawa, Hiroyuki; Sakata, Ryoya; Tanaka, Takashi; Ebihara, Yusuke
Abstract: Direction of the upstream interplanetary magnetic field (IMF) significantly changes the magnetospheric configuration, influencing the atmospheric escape mechanism. This paper investigates effects of IMF on the ion escape mechanism from a Mars‐like planet that has a weak dipole magnetic field directing northward on the equatorial surface. The northward (parallel to the dipole at subsolar), southward (antiparallel), and Parker‐spiral IMFs under present solar wind conditions are compared based on multispecies magnetohydrodynamics simulations. In the northward IMF case, molecular ions escape from the high‐latitude lobe reconnection region, where ionospheric ions are transported upward along open field lines. Atomic oxygen ions originating either in the ionosphere or oxygen corona escape through a broader ring‐shaped region. In the southward IMF case, the escape flux of heavy ions increases significantly and has peaks around the equatorial dawn and dusk flanks. The draped IMF can penetrate into the subsolar ionosphere by erosion, and the IMF becomes mass‐loaded as it is transported through the dayside ionosphere. The mass‐loaded draped IMF is carried to the tail, contributing to ion escape. The escape channels in the northward and southward IMF cases are different from those in the Parker‐spiral IMF case. The escape rate is the lowest in the northward IMF case and comparable in the Parker‐spiral and southward IMF cases. In the northward IMF case, a weak intrinsic dipole forms a magnetosphere configuration similar to that of Earth, quenching the escape rate, while the Parker‐spiral and southward IMFs cause reconnection and erosion, promoting ion escape from the upper atmosphere. Key Points: The ion escape rate is the lowest in northward (parallel) interplanetary magnetic field (IMF) case and comparable in Parker‐spiral and southward (antiparallel) IMF cases In the northward IMF case, ionospheric ions escape from limited regions of the high‐latitude lobe reconnection with a draped IMF In the southward IMF case, IMF penetration into the dayside ionosphere and its subsequent transport to tail flanks cause efficient ion loss